Case report: Translational treatment of unresectable intrahepatic cholangiocarcinoma: Tislelizumab, Lenvatinib, and GEMOX in one case - Zhang, He-wei; Yu, Hai-bo (Frontiers in Oncology, 2024)
Background: Intrahepatic cholangiocellular carcinoma (ICC) is one of the most common invasive malignancies. Currently, ICC is treated with radical surgical resection. However, the majority of patients are diagnosed at an advanced stage, making surgery ineligible for them. Case presentation: We present a case of advanced ICC, which could not undergo radical surgery due to tumor invasion of liver blood vessels. The gemcitabine and oxaliplatin (GEMOX) regimen combined with Tislelizumab immunotherapy and Lenvatinib targeted therapy for 8 cycles resulted in significant tumor shrinkage significantly and the vascular invasion disappeared. CA19-9 levels were reduced to normal levels. Partial remission and successful tumor transformation were achieved. The patient underwent a successful radical surgical resection, including cholecystectomy, resection of liver segments IV, V, and VIII, as well as a regional lymphatic drainage procedure, resulting in complete pathological remission. Conclusion: Tumor-free surgical margins (R0) resection of patients with advanced ICC after combination of immune, targeted and chemotherapy is rare, and there are almost no cases of complete postoperative remission. The GEMOX regimen in combination with Tislelizumab and Lenvatinib has a good antitumor efficacy and safety profile, and may be a feasible and safe translational treatment option for advanced ICC.